in vitro evaluation of the efficiency of Artemisia judaica leaf extract on sporulation of Eimeria papillate oocysts and its cytotoxicity - M.A. Esam; N.M. Saleh; A.G. Rewaida; A.Q.H. Waleed; A. Afaf; A.A. Sarah; Al-Q. Saleh (Arquivo Brasileiro de Medicina Veterinária e Zootecnia)
ABSTRACT Eimeria is the parasite that is responsible for eimeriosis in the gut of numerous domestic mammals. While treating eimeriosis, the use of medication and some effects of synthetic anticoccidials has led to the development of resistant parasites, necessitating the search for alternative treatments. The treatment of a wide variety of parasite diseases can be done with natural products that don't harm the environment. The goal of the current investigation was to determine how Artemisia judaica leaf extract (AJLE) affected the oocyst sporulation of Eimeria papillate strain. Also, reaching the ideal concentration will affect the parasite and limit infection. In vitro: Artemisia judaica leaf extract was applied at four different concentrations (50, 100, 200, and 300mg/mL), while 2.5% potassium dichromate solution served as the control. The sporulation of oocysts was significantly decreased by AJLE, reaching 12.6% at 300mg/mL, and the effect of inhibition on the oocyst sporulation percentages of E. papillata was observed in a dosage-dependent manner in comparison to the control group. Our results revealed that A. judaica has cytotoxic activity against breast and lung cancer cell line with a promising IC50 of 480.3 and 359.2µg/mL, respectively compared to doxorubicin as a standard.